Comparison of germ cell differentiation of rat testis fragments cultured in knockout serum replacement versus Albumax™ I. Issue 4 (21st December 2020) - Nakamura, Noriko; Sloper, Daniel T.
Abstract: Background: Spermatogenesis complexity makes reliable in vitro testis model development challenging. Previously, we evaluated an in vitro mouse testis organ culture system for assessing testicular toxicity. However, rat models are commonly used for drug/chemical toxicity testing; therefore, we assessed the effects of media on germ cell differentiation in cultured rat testis fragments. Methods: Testes from postnatal day 5 Sprague–Dawley (Hsd:SD) rats were cultured in knockout serum replacement (KSR) or Albumax™ I (Albumax) medium. For testis morphology and germ cell differentiation, rat testis fragments were collected on days 20, 27, 35, 42, 49, and 63 of culture for histology/immunohistochemistry using antibodies to spermatogenesis‐specific markers. The fragments collected on days 20, 27, 42, 49, and 63 were used for qPCR. Results: Pachytene spermatocyte (PS) differentiation was observed in rat testis fragments cultured in KSR and Albumax. However, there were more seminiferous tubules (STs) with PS in rat testis fragments cultured in Albumax than in KSR. Over 60% of STs with germ cell differentiation were observed in rat testis fragments when cultured in Albumax on days 20, 27, and 35, whereas this figure showed only on day 20 when cultured in KSR. Conclusions: This study found only PS differentiation in rat testis fragments. Compared to KSR, Albumax appears to contribute to increased PS production. This in vitro rat testis organ culture system may be useful for assessing testicular toxicity. However, PS differentiation per ST is lower in rat testis fragments; further studies are required to improve this rat testis organ culture system.